Мішана задача для нелінійного гіперболічного рівняння в необмеженій області - Лавренюк, С.П.; Панат, О.Т. (Видавничий дім "Академперіодика" НАН України, 2007)
The mixed problem for a hyperbolic equation in an unbounded domain with respect to spatial variables is investigated. Conditions that provide the existence and uniqueness of the solution in generalized Lebesgue spaces are stated. Our results are obtained without any restrictions on the behavior of the initial data and a solution at infinity.